Development of a Structural Model for Predicting Organizational Performance of Bank Employees in Western Tehran Branches Based on Career Path Resilience and Psychological Capital: The Mediating Role of Professional Ethics - Babaloee, Alireza; Molayi Zarandi, Hamid; Kamyabi, Mitra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The objective of the present study was to develop a structural model for predicting the organizational performance of bank employees in the western Tehran branches based on career path resilience and psychological capital, with the mediating role of professional ethics.Methodology: The research method was descriptive-correlational, with a structural equation modeling approach. The statistical population consisted of all bank employees in the western Tehran branches in 2023. The sampling method was convenience sampling. The sample size was 430 individuals, who were evaluated using questionnaires on organizational performance (Andre de Waal et al., 2017), career path resilience (Morgen Lyon, 2001), psychological capital (Luthans, 2007), and professional ethics (Kadous, 2002). The findings were analyzed using structural equation modeling.Findings: Based on the analysis of the research findings, all fit indices derived from the analysis supported the acceptable fit of the structural model with the collected data. The chi-square to degrees of freedom ratio was 2.21, the Comparative Fit Index (CFI) was 0.959, the Goodness of Fit Index (GFI) was 0.938, the Adjusted Goodness of Fit Index (AGFI) was 0.913, and the Root Mean Square Error of Approximation (RMSEA) was 0.057. Additionally, the results showed that career path resilience, psychological capital, and professional ethics together explained 62% of the variance in organizational performance among bank employees.Conclusion: It can be concluded that professional ethics among bank employees mediates the relationship between psychological capital and career path resilience with organizational performance.